2018
DOI: 10.1002/2017jg004312
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Budget for a Peatland Based Upon 13C Solid‐State Nuclear Magnetic Resonance

Abstract: Peatlands can accumulate organic matter into long‐term carbon (C) storage within the soil profile. This study used solid‐state 13C nuclear magnetic resonance (13C‐NMR) to investigate the transit of organic C through a peatland ecosystem to understand the molecular budget that accompanies the long‐term accumulation of C. Samples of biomass, litter, peat soil profile, particulate organic matter, and dissolved organic matter (DOM) were taken from the Moor House National Nature Reserve, a peat‐covered catchment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
5
8
0
Order By: Relevance
“…The C:N ratios found in this study (between 9 and 23) are similar to those found in other studies of peat‐derived DOM and POM, but much lower than those of peat, or of the vegetation found on the peat (25–29 (DOM and POM), median of 52 (peat), and 37 to 58 (vegetation); Armstrong et al., 2015; Clay & Worrall, 2015; Moody et al., 2018). The values are generally higher than those of mineral soils (12.6; Clay & Worrall, 2015), or POM from various UK rivers (9.2–14.3; Worrall, Burt, & Howden, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The C:N ratios found in this study (between 9 and 23) are similar to those found in other studies of peat‐derived DOM and POM, but much lower than those of peat, or of the vegetation found on the peat (25–29 (DOM and POM), median of 52 (peat), and 37 to 58 (vegetation); Armstrong et al., 2015; Clay & Worrall, 2015; Moody et al., 2018). The values are generally higher than those of mineral soils (12.6; Clay & Worrall, 2015), or POM from various UK rivers (9.2–14.3; Worrall, Burt, & Howden, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Solid‐state 13 C‐NMR spectra were recorded at 100.56 MHz using a Varian VNMRS spectrometer and a 4 mm magic‐angle spinning probe at the EPSRC UK National Solid‐state NMR Service at Durham University, using the same method as Moody et al. (2018). The maximum peak height in each eight chemical shift ranges (0–45 ppm C‐alkyl; 45–65 ppm N‐alkyl and methoxyl‐C; 65–95 ppm O‐alkyl‐C; 95–110 ppm O 2 ‐alkyl‐C; 110–145 aromatic/unsaturated C; 145–160 ppm phenolic C; 160–190 ppm carboxyl/amide C; 190–220 ppm aldehyde/ketone C; Baldock & Skjemstad,and Skjemstad, 2000; Hockaday et al., 2009) was divided by the percentage carbon content (from the elemental analysis) to get a relative peak height for each functional group type of carbon observed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work in a United Kingdom blanket bog utilizing the C ox /OR approach along with other analytical techniques (e.g. 13 C‐NMR) shows that polysaccharides are preferentially removed through decomposition leaving behind more lignin‐like compounds in the residual peat (Moody et al., 2018; Worrall et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More recently. Moody et al () have used solid state 13 C‐NMR to give a molecular budget for a peatland and so show that alkyl functional groups were selectively retained.…”
Section: Introductionmentioning
confidence: 99%